Persons with Disabilities Facing the Mirage of the Right to Education: A Systematic Review of the Literature - Díaz Santa María, Yonatan; Molina Saorín, Jesús (Frontiers in Education, 2021)
This article collects the educational path derived from the significant changes that have taken place throughout the recent history of education in Spain and, specifically, in relation to people with disabilities. As a starting point, an analysis is carried out of the transformations that have occurred in the discourse on the education of people with lower functional performance, until a historical approach is reached by virtue of which the different stages and binding educational regulations are revealed (with national and international character), highlighting‒exclusively–those that have a direct impact on the quality of life of people in a situation of disabilities. As can be imagined, the history of education in Spain has evolved as policies have changed their purposes around the diversity of students and their universality in the classroom. In this sense, the need to make visible this new paradigm of human rights derived from the International Convention on the Rights of Persons in a situation of Disabilities (UN, 2006) and, in contrast, the continuity of a national corpus juris that reveals the ineffectiveness of the State and other institutions to extinguish situations of discrimination on the grounds of low functional performance.